The concepts of sakinah, mawaddah and rahmah as foundation for marital happiness according to the Holy Quran: an analysis based on Ayat 21, Surah al-Rum = Konsep Sakinah, Mawaddah dan Rahmah sebagai asas kebahagiaan rumahtangga menurut al-Quran: suatu analisis berdasarkan ayat 21, Surah al-Rum - Ismail, Siti Zubaidah; Awang Mat, Muhamad Zahiri (Brill Academic Publishers, 2016)
As a foundational practice of the Muslim community, one of the objectives of marriage is to procreate and establish a family unit. Therefore, a husband and wife should aspire to foster a relationship as an act of worship towards Allah (SWT). As such, there are many important elements which help to establish the institution of marriage in accordance with Islamic principles. By examining the content of the Holy Qurʾan, several terminologies referring to these elements can be found in various surahs. The more specific concepts mentioned are ‘sakinah’ (tranquility), ‘mawaddah’ (love), and ‘rahmah’ (mercy), all of which can be found mentioned in ayat 21 of Surah al-Rum. This article examines traditional and contemporary Qurʾanic commentaries with regards to this ayat, utilizing hermeneutical and comparative approaches to ascertain the guidelines for both husbands and wives towards nurturing an Islamically ideal marriage.